Efficient Functional Delivery of siRNA using Mesoporous Silica Nanoparticles with Ultralarge Pores - Na, Hee-Kyung; Kim, Mi-Hee; Park, Kihyun; Ryoo, Soo-Ryoon; Lee, Kyung Eun; Jeon, Hyesung; Ryoo, Ryong; Hyeon, Changbong; Min, Dal-Hee (WILEY-V C H VERLAG GMBH, 2012)
Among various nanoparticles, mesoporous silica nanoparticles (MSNs) have attracted extensive attention for developing efficient drug-delivery systems, mostly due to their high porosity and biocompatibility. However, due to the small pore size, generally below 5 nm in diameter, potential drugs that are loaded into the pore have been limited to small molecules. Herein, a small interfering RNA (siRNA) delivery strategy based on MSNs possessing pores with an average diameter of 23 nm is presented. The siRNA is regarded as a powerful gene therapeutic agent for treatment of a wide range of diseases by enabling post-transcriptional gene silencing, so-called RNA interference. Highly efficient, sequence-specific, and technically very simple target gene knockdown is demonstrated using MSNs with ultralarge pores of size 23 nm in vitro and in vivo without notable cytotoxicity.
Keywords: SMALL INTERFERING RNA; ENDOTHELIAL GROWTH-FACTOR; GENE; CELLS; THERAPEUTICS; CANCER; RESISTANT; PLANTS